IWMI taps into local knowledge to build climate resilience in Jordan’s Jerash Camp - Al-Zu’bi, Maha (International Water Management Institute, 2025)
The Integrated Watershed and Climate Risk Hotspot Mapping project, led by the International Water Management Institute (IWMI) with support from CGIAR’s Food Frontiers and Security Program, is uncovering how climate risks are affecting daily life in the Jerash Camp.